2021
DOI: 10.1371/journal.pone.0249780
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study of factors associated with women’s perinatal mental health and wellbeing during the COVID-19 pandemic

Abstract: Pregnant and postpartum women face unique challenges during the COVID-19 pandemic that may put them at elevated risk of mental health problems. However, few large-scale and no cross-national studies have been conducted to date that investigate modifiable pandemic-related behavioral or cognitive factors that may influence mental health in this vulnerable group. This international study sought to identify and measure the associations between pandemic-related information seeking, worries, and prevention behaviors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 43 publications
(47 reference statements)
12
131
1
4
Order By: Relevance
“…A survey of pregnant women and postpartum women during the pandemic, showed that 40% of participants suffered from post-traumatic stress disorder and around 70% suffered from depression and/or anxiety following the onset of the new virus [ 62 ]. It is also in line with the results found in a systematic review that summarized the increase of mental disorders in pregnant women caused by this pandemic [ 63 ]. In contrast, previous studies have shown a prevalence of depression lower than 60% [ 43 , 45 , 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…A survey of pregnant women and postpartum women during the pandemic, showed that 40% of participants suffered from post-traumatic stress disorder and around 70% suffered from depression and/or anxiety following the onset of the new virus [ 62 ]. It is also in line with the results found in a systematic review that summarized the increase of mental disorders in pregnant women caused by this pandemic [ 63 ]. In contrast, previous studies have shown a prevalence of depression lower than 60% [ 43 , 45 , 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…A recent large-scale international survey of pregnant women revealed that about half of the women reported increased feelings of loneliness during the COVID-19 pandemic. 12 In a study of the Spanish population during the initial stage of the COVID-19 pandemic, loneliness was correlated with depression, anxiety, and post-traumatic stress disorder. 13 Social support has been identified as a major protective factor against negative mental health outcomes resulting from natural disasters and pandemics, 14 , 15 and recent evidence suggests that it is also associated with lower mental health symptoms in pregnant women during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Women who reported higher levels of loneliness also reported higher levels of perceived stress and depressive symptoms. Similarly, loneliness was related to stress and depressive symptoms during the COVID-19 pandemic among pregnant women (Basu et al, 2021;Perzow et al, 2021). Health care providers should recommend pregnant women to talk with family and friends (e.g., phone calls, FaceTime, Zoom), maintain a healthy lifestyle (e.g., walking outside while maintaining social distance, getting quality sleep, healthy diet), and participate in virtual support groups for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Research about loneliness during the pandemic is limited among pregnant women. In a sample of 6,894 pregnant and postpartum women from 64 countries who completed an online survey in May-June 2020 (18% from North America, 8% Black, no data on how many pregnant Black women from the United States), 54% of women had high levels of loneliness (Basu et al, 2021). In a study with 135 pregnant women from Colorado (n = 15 Black), higher levels of loneliness were associated with increased depressive symptoms during the COVID-19 pandemic (data collection April-May 2020) (Perzow et al, 2021).…”
Section: Loneliness During the Covid-19 Pandemicmentioning
confidence: 99%